2022
DOI: 10.3390/ijerph191811213
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Abdominal Adiposity and Physical Fitness on Obesity Status of Portuguese Adolescents

Abstract: The aim of this study was to verify the relationship between abdominal adiposity and physical fitness in the obesity status of Portuguese adolescents. BMI, abdominal adiposity, and physical fitness tests from the FITescola® were evaluated in a total of 654 Portuguese adolescents, aged 10-19 years old—male: n = 334 (51%), female: n = 320 (49%). For the final model, BMI was positively related with age (β = 0.25), abdominal adiposity (β = 0.313), horizontal jump (β = −0.100), 40 m maximal velocity (β = 0.274), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
1
1
Order By: Relevance
“…Furthermore, the present study indicates that, possibly, both sex presented negative health behaviors at some point in their childhood and adolescence [ 8 ]. In addition, despite the moderate effect size influence favoring better physical fitness for boys, the prevalence of obesity in both sex were high (44% in boys and 41% in girls), without significant differences between sex rates, and higher than our previous findings (18% in boys, and 20% in girls) [ 13 ]. Regarding these inferences, it becomes clear that, beyond the statistical differences, the cut-offs reveal that there is still a great risk for the physical and mental health of adolescents [ 6 ].…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the present study indicates that, possibly, both sex presented negative health behaviors at some point in their childhood and adolescence [ 8 ]. In addition, despite the moderate effect size influence favoring better physical fitness for boys, the prevalence of obesity in both sex were high (44% in boys and 41% in girls), without significant differences between sex rates, and higher than our previous findings (18% in boys, and 20% in girls) [ 13 ]. Regarding these inferences, it becomes clear that, beyond the statistical differences, the cut-offs reveal that there is still a great risk for the physical and mental health of adolescents [ 6 ].…”
Section: Discussioncontrasting
confidence: 82%
“…Furthermore, epidemiological data have shown that sex differences in obesity are more pronounced in low-income countries [ 11 ]. In Portugal, the research on modifiable and non-modifiable factors in the incidence and prevalence of obesity and sex influences is limited [ 12 , 13 ]. Therefore, conducting studies that analyze the influence of sex could provide valuable insights to enhance the quality and quantity of information on this topic, thereby stimulating new perspectives and comprehensive implications for research on obesity and its modifiable and non-modifiable factors in Portuguese adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we did not find any previous study which has investigated obesity risk in Portuguese adolescents. In addition, we published preliminary results about the relationship between lower physical fitness and obesity in Portuguese adolescents [31]; however, we have unknown studies performing NNET or similar predictive validation techniques in childhood and adolescence obesity screening at a national level. Different to conventional regression analysis, DL models, when well trained, produce more robust generalization capability, which is very valuable in real life.…”
Section: Introductionmentioning
confidence: 99%